2016
DOI: 10.1002/ehf2.12086
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a novel non‐contact monitor of nocturnal respiration for identifying sleep‐disordered breathing in patients with heart failure

Abstract: AimsAt least 50% of patients with heart failure (HF) may have sleep‐disordered breathing (SDB). Overnight in‐hospital polysomnography (PSG) is considered the gold standard for diagnosis, but a lack of access to such testing contributes to under‐diagnosis of SDB. Therefore, there is a need for simple and reliable validated methods to aid diagnosis in patients with HF. The aim of this study was to investigate the accuracy of a non‐contact type IV screening device, SleepMinderTM (SM), compared with in‐hospital PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…27,28 Even though a large number of studies has been published in recent years, screening (polygraphy, questionnaires) and monitoring (e.g. SleepMinder TM ) 29 tools remain under-utilized. Unfortunately, one of the few larger randomized controlled trials, the SERVE-HF trial, 30 ended in disappointment, and it appears unlikely that adaptive servo-ventilation will be used in patients with HF in future trials or in clinical practice.…”
Section: Atrial Fibrillation ≈30%mentioning
confidence: 99%
“…27,28 Even though a large number of studies has been published in recent years, screening (polygraphy, questionnaires) and monitoring (e.g. SleepMinder TM ) 29 tools remain under-utilized. Unfortunately, one of the few larger randomized controlled trials, the SERVE-HF trial, 30 ended in disappointment, and it appears unlikely that adaptive servo-ventilation will be used in patients with HF in future trials or in clinical practice.…”
Section: Atrial Fibrillation ≈30%mentioning
confidence: 99%
“…2009-2016 [17,47,48] Cheyne-Stokes Respiration Correlation coefficient of 0.87 with %CSR > 5 and 0.8 with AHI > 15.…”
Section: Challenges and Future Research Directionsmentioning
confidence: 99%
“…There have also been numerous reviews, comparison studies [16][17][18][19], and smart systems designs [20,21] regarding unobtrusive [22], nonintrusive [23], and non-contact physiological vital signs monitoring for sleep monitoring. However, a comprehensive review of the non-contact Doppler radar for health monitoring for OSA diagnosis has been limited.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with HF, many different co‐morbidities can influence the patients' burden of disease . Common co‐morbidities in patients with HF include iron deficiency, anaemia, liver dysfunction, chronic kidney disease, central sleep apnoea, chronic obstructive pulmonary disease, sexual dysfunction, cachexia, sarcopenia, anorexia, and also cancer . Professor Rudolf De Boer from Groningen, the Netherlands, presented several studies, which have shown that cancer patients have an increased risk to develop HF and that patients with both, cancer and HF, demonstrate even worse prognosis than both diseases alone .…”
Section: The Intersection Between Cardiology and Oncologymentioning
confidence: 99%